Advanced Biowaste‐Based Flexible Photocatalytic Fuel Cell as a Green Wearable Power Generator. Issue 3 (21st December 2016) - Lui, Gregory; Jiang, Gaopeng; Lenos, Jared; Lin, Edric; Fowler, Michael; Yu, Aiping; Chen, Zhongwei
Abstract : This study designs a wearable power generator from a flexible, photocatalytic fuel cell (fPFC) using various biowaste sources (lactic acid, ethanol, methanol, urea, glycerol, and glucose) as fuel. The fPFC uses light irradiation and the decomposition of biowaste to generate electrical power under both flat and bending ( r = 3 cm) conditions. When employed as a sweat band, the fPFC generates a maximum power 4.0 mW cm −2 g −1 from human sweat. The wearable fPFC is able to overcome many of the disadvantages of wearable microbial and enzymatic cells while providing comparable if not superior power density. Abstract : A wearable power generator is designed from a flexible, photocatalytic fuel cell (fPFC) using various biowaste sources as fuel . The fPFC uses light irradiation and the decomposition of biowaste to generate electrical power under both flat and bending conditions. When employed as a sweat band, the fPFC generates a maximum power 1.6 mW cm −2 g −1 from human sweat.